Debt, Deficits, and Destabilizing Monetary Policy in Open Economies - Andreas Schabert; Sweder van Wijnbergen (Tinbergen Institute, 2006)
Blanchard (2005) suggested that active interest rate policy might induce unstable dynamics in highly-indebted economies. We examine this in a dynamic general equilibrium model where Calvo-type price rigidities provide a rationale for inflation stabilization. Unstable dynamics can occur when the CB is aggressively raising the interest rate in response to higher expected inflation. The constraint on stabilizing interest rate policy is tighter the higher the primary deficit and the more open the economy is. If the government cannot borrow from abroad in its own currency, stability requires interest rate policy to be accommodating (passive). Inflation stabilization is nevertheless feasible if the CB uses an instrument not associated with default risk, e.g. money supply.
Keywords: E52; E63; F41; 330; Fiscal-monetary policy interactions; sovereign default risk; foreign debt; inflation targeting; original sin